An Analysis Of Illocutionary Acts On Anies Baswedan’s Last Speech From Governorship Of DKI Jakarta - Ismi Adinda; Nurdin Nurdin (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
The goal of this research is to provide an overview of the types and goals of illocutionary acts that Anies Baswedan delivered in his farewell speech from governorship of DKI Jakarta on Sunday, October 16, 2022. The research being conducted offers descriptive methods with a qualitative approach. Speech serves as the study's primary source of data. by containing illocutionary speech acts on Anies Baswedan's farewell speech from DKI Jakarta governorship. Researchers use Leech's theory and Searle's theory for clarification of the various types of illocutionary acts. The research data is the video of Anies Baswedan which is downloaded via YouTube. The data was collected by listening to Anis Baswedan speak and transcribing the speech into writing. Utilizing trilingual, the veracity of the data is determined. Data analysis consisted of (1) converting the recorded data into written language, (2) categorizing the data based on the type of further investigation illocutionary speech, and (3) analyzing the results. (3) analyzing the data that have been classified, (4) make the conclusion of the research results based on data from this study. After this study, researchers aimed to be able to enhance the knowledge of illocutionary act among lecturers, students, and readers